Mechanical Circulatory Support in Management of Cardiogenic Shock and Myxedema Coma. (6th March 2019) - Arnautovic, Jelena Z.; Connor-Schuler, Randi; Ip, Randy
Abstract : The cardiovascular system is a major target of thyroid hormone action and the two systems are closely interlinked. It can be greatly impacted even with subtle alterations in thyroid function. Caution is needed when implementing thyroid hormone replacement in patients with severe hypothyroidism, especially in the setting of ischemic coronary artery disease. If not properly treated, myxedema may ensue. Given the high mortality of myxedema coma, supportive care may not always suffice and patients may require more invasive interventions. We present a challenging case of a patient with overt hypothyroidism with concurrent acute coronary syndrome which subsequently lead to myxedema coma and cardiogenic shock. A transcaval approach for the delivery of an Impella 5.0 (Abiomed Inc., Danvers, MA) was utilized in supporting this patient. To our knowledge, this is the first reported case that describes the use of a mechanical circulatory support in treating myxedema-induced cardiovascular collapse.